IMPLIKASI PANDANGAN DIKOTOMI DALAM KEHIDUPAN KRISTEN - Jimmy Sugiarto (Jurnal Pistis: Teologi dan Praktika, 2021)
The view of human structure influences actions living the Christian life. One theological view of the human structure is a dichotomy. This view recognizes that humans consist of a physical body and a soul as an immaterial element. This study describes the impact of the dichotomous view on the behavior of believers in responding to Bible truth. This study presents the process of exegesis of the book of Genesis 2:7 and extracts from the thoughts of scholars.